PENGARUH PROMOTIONAL MIX TERHADAP KEPUTUSAN KONSUMEN MEMBELI SARUNG SAMARINDA PADA KUB SEJAHTERA PADAIDI DI SAMARINDA - Syaiful Ibrahim; Suharno Suharno; Asnawati Asnawati (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The purpose of this study to know the effect of advertising on the consumer's decision to buy gloves Samarinda on KUB Prosperous Padaidi In Samarinda, know the effect of sales promotions on the consumer's decision to buy gloves Samarinda on KUB Prosperous Padaidi In Samarinda and know the effect of PR on the consumer's decision to buy gloves Samarinda on KUB Prosperous Padaidi In Samarinda. Digunkan basic theory of marketing management by using multiple linear regression analysis with 50 samples .The conclusion of this study:T value variable rent is greater than t table and the significance of less than 0.05. These results indicate that the variable advertising program created by KUB Prosperous Padaidi In Samarinda sifnifikan has influence the consumer decision Samarinda sarongs on KUB Prosperous Padaidi In Samarinda. The study hypothesis is acceptedT value variable Sales Promotion greater than t table significance of less than 0.05. These results indicate that the sales promotion variables that influence consumer buying decisions sifnifikan Samarinda sarongs on KUB Prosperous Padaidi In Samarinda. The study hypothesis is acceptedPR variable t value greater than t table and the significance of less than 0.05. These results indicate that variable sifnifikan PR has influence on consumer buying decisions at the KUB Prosperous Samarinda sarongs Padaidi In Samarinda. The study hypothesis is acceptedKeywords: Promotion Mix - Consumer Decision